Balloon remodeling-assisted Woven EndoBridge technique: description and feasibility for complex bifurcation aneurysms. (5th October 2018) - Mihalea, Cristian; Escalard, Simon; Caroff, Jildaz; Ikka, Léon; Rouchaud, Aymeric; Da Ros, Valerio; Pagiola, Igor; Marenco de la Torre, Joaquin Jose; Yasuda, Thomas; Popa, Bogdan Valeriu; Ples, Horia; Benachour, Nidhal; et al.
Abstract : Background: Woven EndoBridge (WEB) deployment remains challenging in aneurysms with a complex shape or orientation. Objective: To show that embolization of wide-neck bifurcation aneurysms using the WEB device balloon remodeling-assisted technique is a feasible and elegant endovascular solution compared with other techniques, such as balloon remodeling or stent-assisted coiling. Materials and methods: 10 cases (10 aneurysms in 9 patients) of balloon remodeling-assisted WEB treatment of unruptured complex bifurcation aneurysms were treated in our institution and retrospectively analyzed. Details of clinical presentations, technical details, perioperative and postoperative complications, and outcomes were collected. Immediate and long-term angiographic results were also evaluated. Results: Aneurysms included six middle cerebral artery aneurysms, one anterior communicating artery aneurysm, one posterior communicating artery aneurysm, one basilar artery aneurysm, and one T-shaped carotid aneurysm. Mean dome width was 6.55 mm, mean neck size 4.5 mm, mean height 4.79 mm, and mean dome-to-neck ratio was 1:1.46. Treatment was performed exclusively with the balloon remodeling-assisted WEB technique in all cases. The device was successfully deployed in every case. Periprocedural thromboembolic or hemorrhagic events did not occur. The modified Rankin Scale score at discharge was 0 for all patients. At mid-term or long-term angiographic follow-up, adequate occlusion was observed in 7 aneurysms from 8 controlled cases (87.5%), and one patient (2 aneurysms) did not have angiographic follow-up. Conclusion: The balloon remodeling-assisted WEB technique seems to be a safe and effective solution for endovascular treatment of unruptured wide-neck bifurcation aneurysms with specific complex anatomy. However, further studies are needed to evaluate the rate of complications and long-term efficacy.